Різноманітність за локусами запасних білків популяцій Aegilops biuncialis Vis. західного узбережжя Криму - Козуб, Н.О.; Созінов, І.О.; Бідник, Г.Я.; Дем'янова, Н.О.; Созінов, О.О. (Фактори експериментальної еволюції організмів, 2014)
Aims. The objective of the investigation was analysis of genetic diversity of Ae. biuncialis populations from the Western coast of the Crimea. Methods. Samples from natural populations of Beregove (Bakhchisarai region) and Sevastopol were analyzed. SDS electrophoresis of high-molecular-weight glutenin subunits and APAG electrophoresis of gliadins were used to identify alleles at the Gli-U1, Gli-Mb1, Glu-U1, Glu-Mb1 loci. Results. Frequencies of alleles at the storage protein loci in two populations of Ae. biuncialis and genic variation statistics were determined. The populations were characterized with respect to predominant alleles. Conclusions. The Ae. biuncialis populations from the Western coast of the Crimea show similarly high values of genic diversity at the storage protein loci but significantly differ in the predominant alleles and their frequency. These data can be used for the monitoring of the state of diversity of Ae. biuncialis populations of the Western coast of theCrimea.

Key words: Aegilops biuncialis, diversity, storage proteins, alleles.